The choice of building contract parameters by competition/Statybos kontraktų parametrų parinkimas konkursui - Ginevičius, Romualdas; Čirba, Stasys (Journal of Civil Engineering and Management, 1998)
When implementing any project (not only in building construction), we face a perpetual problem of how to combine three essential and contradictory conditions: price, duration and quality. It is the so-called problem of golden triangle. In competitions with many participants, the winner is the contractor who makes considerable concession to the client. However, when such concessions are extremely large, the competition can be won, but the probability of contract implementation failure may greatly increase. On the other hand, in case of a higher price and duration one may yield to other competitors. Therefore the participants of a competition always encounter the problem to offer such values of the above-mentioned parameters which provide the greatest probability of winning the competion under the most favourable conditions for the contractor. In order to solve the problem, it is necessary to know the interrelations of contract parameters discussed. The analysis of data presented in some References provided the possibility to determine the dependency of the contract price on the implementation time. The investigations show that the dependency of quality is analogous with the price dependency. Having established the summary dependency of the price and quality on time, it is possible to find the change in time of contract profit amount. The analysis showed that this dependency is contrary to the above-mentioned summary dependency. By depicting in a profit way these interdependencies, it is possible to look for such values of essential contract parameters (price, duration and quality) which can ensure winning the competion and the profit planned. Article in Lithuanian. First Published Online: 26 Jul 2012